PERBEDAAN HASIL BELAJAR IPA-BIOLOGI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TPS (THINK PAIR SHARE) DAN MODEL PEMBELAJARAN JIGSAW SISWA KELAS VIII SMP NEGERI 2 KARTASURA TAHUN PELAJARAN 2013/2014 - Asti Dwi Lestari; Djumadi Djumadi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
This study is an experimental study that aims to identify differences in learning outcomes through cooperative learning model of TPS ( Think Pair Share ) and use the model of Jigsaw the subject 's body structure plant eighth grade students of SMP Negeri 2 Kartasura . Classes used in this study were three classes, randomly selected. Class used different study treated with the same material. Data collection techniquesin this study using the methods of documentation, observation, and post test. Analyze data using a statistical test of test validity,reliability,degree of difficulty, different power matter, normality, homogenity, and to test hypotheses using Kruskal-Wallis and Mann-Whitney U Test, assisted by SPSS 15.0 for Windows. Average cognitive learning outcomes VIIIG class with TPS models of 80.5 is lower than the class of models that use Jigsaw by 81 and conventional by 72. Results of the Kruskal-Wallis test hypotheses using model learning Jigsaw-TPS and obtained 0,000 < 0,05, then H0 is rejected so there is a difference between learning outcomes learning TPS, Jigsaw and control.Further test results using the Mann-Whitney U Test results of TPS-Jigsaw obtained 0.760 > 0.05 so H0 is accepted; Control stations obtained 0.000 < 0.05 H0 is rejected; Jigsaw-control obtained 0.000 < 0.05 H0 is rejected. Based on the results of the analysis ofthese data can be obtained conclusion: there are differences in learning outcomes between TPS learning models, Jigsaw, and Conventional (lectures) on the subjects of biological material of plant body structure Junior High School eighth grade 2 Kartasura academic year 2013/2014. The most effective learning jigsaw model used in the learning process plant material body structure compared to the learning model TPS (Think Pair Share) and lectures (conventional) in the eighth grade students of SMP Negeri 2 Kartasura academic year 2013/2014. Keywords: TPS models, jigsaw models, results of learning